Security-Aware Design for Cyber-Physical Systems A Platform-Based Approach - Lin, Chung-Wei; Sangiovanni-Vincentelli, Alberto (Springer International Publishing : Imprint: Springer, 2017)
Addressing the rising security issues during the design stages of cyber-physical systems, this book develops a systematic approach to address security at early design stages together with all other design constraints. Cyber-attacks become more threatening as systems are becoming more connected with the surrounding environment, infrastructures, and other systems. Security mechanisms can be designed to protect against attacks and meet security requirements, but there are many challenges of applying security mechanisms to cyber-physical systems including open environments, limited resources, strict timing requirements, and large number of devices.  Designed for researchers and professionals, this book is valuable for individuals working in network systems, security mechanisms, and system design. It is also suitable for advanced-level students of computer science. .